Social worker intervention in the socio-emotional well-being of older adults - Intriago-Molina, Gema Beatriz (2021)
Currently the ageing of the elderly population is a challenge in society, this population is highly vulnerable in the family and social environment. Being an elderly means being cared for, respected, protected and supported by the family. The objective of the research was to analyze the intervention of the social worker in the socio-emotional well-being of the elderly, using quantitative and qualitative methodology and interview and survey techniques a survey 30 applied to users of the Santa Gema de Galgani Gerontological Center of the Abdón Calderón Parish from Portoviejo and an interview with the social worker. The results show that most of the older adults live with their relatives while there is a minor percentage who live by themselves, despite this, there is some evidence of lack of communication with their family members due to their work responsibilities, but when they are in situations of need they are efficiently cared for, It is concluded that, the intervention of the social worker is focused on optimizing the quality of life of the elderly, they carry out activities that favor their socio-emotional well-being, relying on methods, techniques and instruments of the profession such as the Barthel index, the Lawton and Brody scale and the mini mental test, which are the starting point for the development of activities that favor the improvement of their quality of life.